The Multifaceted Impact of Dietary Habits on Mental and Physical Health: Insights into Socio-Economic, Cultural, and Technological Influences on Young Populations - Gurjar, Krishna; Dwivedi, Shaurya; Samtani, Heena; Padaliya, Om; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R. (Dinasti Health and Pharmacy Science, 2024)
This study examines the multifaceted impact of dietary habits on the mental and physical health of young populations, highlighting the influence of socio-economic, cultural, and technological factors. Recent research indicates that poor dietary choices are linked to various health issues, including obesity, anxiety, and depression. The analysis reveals a lack of significant differences in health metrics among participants, emphasizing the need for targeted interventions and educational programs. Future research should focus on longitudinal studies and the role of technology in promoting healthy eating. The findings underscore the global importance of improving dietary habits among youth to combat rising rates of non-communicable diseases and enhance overall well-being.